TANGGUNG JAWAB PEMBAYARAN UANG MUKA DAN RISIKO KORUPSI KERUGIAN KEUANGAN NEGARA DALAM PROYEK PEMBANGUNAN JALUR TRANSMISI LISTRIK - Wijaya, Firman; Triyanto, Slamet (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The development of electricity infrastructure, especially electricity transmission line projects, is an important part of supporting national economic growth. However, in its implementation, the project often faces legal problems, especially related to down payments that can have implications for the risk of corruption and state financial losses. The down payment given by the employer to the contractor is intended to accelerate the implementation of the work, but in practice it is often misused, either due to weak supervision, breach of contract, or lack of adequate guarantees. This study aims to analyze the legal responsibility in down payment payments and identify the potential for corruption that can arise due to deviations in its use. The method used is normative juridical with a conceptual approach and laws and regulations. The results of the study show that in the 150 kV T/L transmission construction project in West Sulawesi by PT PLN (Persero), it was found that down payments had been made in accordance with the provisions of laws and regulations. However, the contractor was only able to complete a small part of the work, namely 33 of the 81 foundation points, before the project was unilaterally stopped. This failure has the potential for state losses due to the lack of progress commensurate with the down payment that has been paid, as well as the weak realization of the down payment guarantee. In addition, the absence of contract termination in accordance with legal procedures and the absence of sanctions against service providers strengthens the indication of administrative negligence and the potential for corruption. Therefore, it is necessary to strengthen the legal aspects in the construction contract clauses, as well as strict supervision in the distribution and use of down payments so that national strategic projects are implemented in an accountable and transparent manner.